Rock toppling assessment at Mugling-Narayanghat road section: a case study from Mauri Khola landslide, Nepal - Regmi, Amar Deep; Yoshida, Kohki; Nagata, Hidehisa; Pradhan, Biswajeet (Elsevier, 2014)
Mugling–Narayanghat road section in Nepal has suffered from a variety of slope failure including rockslides, rock topples, debris slide/flow, and some combination of these. Based on the prominent type of failure, the highway can be divided into three sections (a) Ch10 to Ch17 (dominated by shallow landslides and debris slides/flows), (b) Ch17 to Ch28 (dominated by large-scale, deep-seated landslides), and (c) Ch28 to Ch35 (dominated by rock topples). Rock topples are frequently observed along the highway, mainly on both the limbs of Jalbire Syncline as well as at the upstream of Maure Khola and some in Siwaliks. Slates, phyllites, quartzite, amphibolite and sandstones are affected by these topples. The Maure Khola landslide that is highly affected by rock toppling falls in Nourpoul Formation and consists of amphibolite, quartzite, and slate/phyllite. It lies at the upper reach of the Simaltal Thrust. Steep slopes characterize the upper slope, whose base is covered by thick debris forming a huge debris fan. According to the selected methodological approaches, data from detailed geological, geomorphological and geomechanical surveys, it is clear that these topples are mainly related to the geological structures of the region. Additionally, the landslide contains several sheared zones where the rocks are considerably weathered. These sheared zones act as the sliding plane. Also, the debris fan at the lower part suggests that the landslide has been reactivated several times in the past. Furthermore, it is seen that flexural toppling occurs in weak, mica-rich slate/phyllite at the upper slope, while block toppling is prominent in stronger amphibolites and quartzite lying in the central part.